La cara oculta del cine - Soublette, Gastón (Ediciones Universidad Católica de Chile, 2011)
Author Gastón Soublette is a philosopher, writer and musician. He is also a movie lover and a specialist of the Mapuche and Eastern beliefs. He states that movies have a "hidden side" and presents in this edition his hermeneutic vision on 11 classic films.